Post-truth and Islamophobia narration in the contemporary Indonesian political constellation - Zainuddin Syarif; Syafiq A. Mughni; Abd Hannan (Indonesian Journal of Islam and Muslim Societies, 2020)
This article discusses the phenomenon of post-truth politics, role, and its influence on the return of Islamophobic narratives in the dynamics of Indonesian political constellation. There are three main issues discussed in this study: post-truth, Islamophobia in Indonesia, and contemporary Indonesian political constellation. Using qualitative research and analysis of critical theory perspectives, this study found that the development of post-truth political practices indirectly evokes the narrative of Islamophobia in contemporary Indonesian political constellation. The return of the Islamophobia can be seen in three ways. First, the practice of post-truth politics which is rooted in the politicization of religion and ethnicity, it gives negative impact not only because of unhealthy process of leadership circulation in Indonesia, but has also faltered the reality of Indonesia's plurality as a pluralist state, both in terms of ethnicity and religion. Second, post-truth political practices in which contain propaganda, intimidation, lies and hate speech have stimulated the rise of sentiment towards religious social groups, as happened in the “212 Movement”. Third, the return of Islamophobic narratives due to political Post-truth appears to be increasing clashes and practices of religious intolerance in Indonesia, where intolerance is practiced by the majority against minority groups. Artikel ini mengkaji fenomena politik post-truth, peran dan pengaruhnya terhadap kembalinya narasi Islamophobia dalam dinamika konstelasi politik Indonesia kontemporer. Terdapat tiga permasalahan pokok yang dibahas dalam kajian ini: post-truth, Islamophobia, dan konstelasi politik Indonesia kontemporer. Dengan menggunakan jenis penelitian kualitatif dan analisis perspektif teori kritis, studi ini mendapati temuan bahwa berkembangnya praktik politik post-truth, secara tidak langsung telah membangkitkan kembali narasi Islamophobia dalam konstelasi politik Indonesia kontemporer. Kembalinya narasi Islamophobia tersebut terlihat dalam tiga hal. Pertama, praktik politik post-truth yang berakar pada politisasi agama dan etnisitas, telah menimbulkan dampak negatif bukan saja pada tidak sehatnya proses sirkulasi kepemimpinan di Indonesia, namun juga telah membuat goyah realitas kemajemukan Indonesia sebagai negara pluralis, baik dari segi etnisitas maupun agama. Kedua, praktik politik post-truth yang di dalamnya berisikan propaganda, intimidasi, dan kebohongan, telah menstimulus bangkitnya sentimen terhadap kelompok-kelompok sosial keagamaan, seperti yang terjadi dalam gerakan Aksi Bela Islam 212. Ketiga, kembalinya narasi Islamophobia akibat politik post-truth nampak pada semakin meningkatnya benturan dan praktik intoleransi keagamaan di Indonesia, di mana intoleransi dilakukan oleh kelompok mayoritas terhadap kelompok minoritas.